2019
DOI: 10.1002/cm.21560
|View full text |Cite
|
Sign up to set email alerts
|

The MyMOMA domain of MYO19 encodes for distinct Miro‐dependent and Miro‐independent mechanisms of interaction with mitochondrial membranes

Abstract: MYO19 interacts with mitochondria through a C‐terminal membrane association domain (MyMOMA). Specific mechanisms for localization of MYO19 to mitochondria are poorly understood. Using promiscuous biotinylation data in combination with existing affinity‐capture databases, we have identified a number of putative MYO19‐interacting proteins. We chose to explore the interaction between MYO19 and the mitochondrial GTPase Miro2 by expressing mchr‐Miro2 in combination with GFP‐tagged fragments of the MyMOMA domain and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 115 publications
(230 reference statements)
3
34
0
Order By: Relevance
“…While stable subplasmalemmal actin rings form periodic structures that wrap around axons to support the axonal membrane, dynamic intra-axonal filaments help to enrich actin at presynaptic terminals (Ganguly et al, 2015;Xu, Zhong, & Zhuang, 2013). It has been reported that mitochondrial receptors Miro1/2 regulate recruitment and stability of myosin-19, thus likely coordinating MT-and actin-based mitochondrial trafficking in mouse embryonic fibroblasts (MEFs) (Bocanegra et al, 2020;López-Doménech et al, 2018;Oeding et al, 2018;Quintero et al, 2009). However, the role of myosin-19 in axonal mitochondrial trafficking is not clear.…”
Section: Regulation Of Axonal Mitochondrial Motilit Ymentioning
confidence: 99%
“…While stable subplasmalemmal actin rings form periodic structures that wrap around axons to support the axonal membrane, dynamic intra-axonal filaments help to enrich actin at presynaptic terminals (Ganguly et al, 2015;Xu, Zhong, & Zhuang, 2013). It has been reported that mitochondrial receptors Miro1/2 regulate recruitment and stability of myosin-19, thus likely coordinating MT-and actin-based mitochondrial trafficking in mouse embryonic fibroblasts (MEFs) (Bocanegra et al, 2020;López-Doménech et al, 2018;Oeding et al, 2018;Quintero et al, 2009). However, the role of myosin-19 in axonal mitochondrial trafficking is not clear.…”
Section: Regulation Of Axonal Mitochondrial Motilit Ymentioning
confidence: 99%
“…The three IQ-motifs bind regulatory light chains (RLCs) of non-muscle and smooth muscle myosin 2 ( Lu et al, 2014 ). The relatively short tail region (146 aa in human Myo19) is unique and responsible for binding to mitochondria through an interaction with lipids ( Hawthorne et al, 2016 ; Shneyer et al, 2016 ) and Miro ( López-Doménech et al, 2018 ; Oeding et al, 2018 ; Bocanegra et al, 2020 ). Interestingly, the dissociation of Myo19 from Miro leads to its degradation ( López-Doménech et al, 2018 ; Oeding et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is supported by the fact that Ahnak1 is an interaction partner of myosin XIX (MYO19) that is associated with the mitochondrial outer membrane. 61 , 62 , 63 Our results showed that Ahnak1 is localized on the mitochondrial membrane, most likely at the outer mitochondrial membrane, and thus serves as a novel mitochondrial‐associated‐membrane protein. Based on the data obtained in this study, we assume that Ahnak1 binds to the contact sites on the mitochondrial membrane required for mitochondrial fusion, possibly masking these sites, which could disturb the mitochondrial fusion process.…”
Section: Discussionmentioning
confidence: 67%